2014
DOI: 10.1007/s11605-014-2520-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Standardized Clinical Pathways: Refining Multidisciplinary Care and Process to Improve Outcomes of the Surgical Treatment of Esophageal Cancer

Abstract: The results of this study show that process improvement within the pathway is likely more significant than the level of comorbidities, application of neoadjuvant chemoradiation, or technical approach in patients undergoing esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 44 publications
0
49
1
Order By: Relevance
“…In contrast to the often quoted 5% or higher mortality rate with local and regionally advanced tumors, recent publications from high-volume centers have reported that esophagectomy can be performed in patients with early esophageal neoplasia with a mortality rate of 0% to 1%, well below the average risk of nodal disease in these patients [20,21]. Furthermore, a true preoperative determination of the depth of invasion and, therefore, isolation of a patient population with low risk of nodal disease may not be possible.…”
Section: Commentmentioning
confidence: 83%
“…In contrast to the often quoted 5% or higher mortality rate with local and regionally advanced tumors, recent publications from high-volume centers have reported that esophagectomy can be performed in patients with early esophageal neoplasia with a mortality rate of 0% to 1%, well below the average risk of nodal disease in these patients [20,21]. Furthermore, a true preoperative determination of the depth of invasion and, therefore, isolation of a patient population with low risk of nodal disease may not be possible.…”
Section: Commentmentioning
confidence: 83%
“…We recently published the outcomes of 595 patients managed according to our SCP after esophagectomy with a median LOS of 8 days in the last 4 years of the study period [11]. We identified a subgroup of patients that exceeds even our aggressive discharge goal of day 7.…”
mentioning
confidence: 99%
“…In addition to surgeon performance and hospital volume, the outcomes of highly complex surgical procedures such as esophagectomy rely heavily on staff from other hospital units and services, including the anesthetic team, ICU caregivers, nurses, nutritionists, and physical therapists (16,17). Strategies to minimize morbidity and mortality should be advocated, from preoperative patient selection to the implementation of standardized perioperative and multidisciplinary care pathways (18).…”
Section: Discussionmentioning
confidence: 99%